2017
DOI: 10.1371/journal.pone.0185437
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence, characterization, and potential predictors of verotoxigenic Escherichia coli, Listeria monocytogenes, and Salmonella in surface water used for produce irrigation in the Lower Mainland of British Columbia, Canada

Abstract: Produce has become a major source of foodborne illness, and may become contaminated through surface water irrigation. The objectives of this study were to (i) determine the frequency of verotoxigenic E. coli (VTEC), Listeria monocytogenes, and Salmonella in surface waters used for irrigation in the Lower Mainland of British Columbia, (ii) assess the suitability of fecal coliforms and generic E. coli as hygiene indicators, and (iii) investigate the correlations of environmental factors with pathogen occurrence.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
46
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(57 citation statements)
references
References 54 publications
9
46
1
1
Order By: Relevance
“…The identification of an association between year-day and microbial water quality suggests that microbial water quality varied seasonally, which is consistent with the findings of previous studies (Carter et al, 1987; Cooley et al, 2014; Falardeau et al, 2017; Gorski et al, 2011; Horman et al, 2004; Wilkes et al, 2009). For example, Falardeau et al (Falardeau et al, 2017) reported that L. monocytogenes was more prevalent in winter than summer in agricultural watersheds in British Colombia, Canada. Similarly, Cooley et al (Cooley et al, 2014) found that the likelihood of isolating L. monocytogenes from California surface water samples was significantly higher in winter and spring compared to summer and fall.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…The identification of an association between year-day and microbial water quality suggests that microbial water quality varied seasonally, which is consistent with the findings of previous studies (Carter et al, 1987; Cooley et al, 2014; Falardeau et al, 2017; Gorski et al, 2011; Horman et al, 2004; Wilkes et al, 2009). For example, Falardeau et al (Falardeau et al, 2017) reported that L. monocytogenes was more prevalent in winter than summer in agricultural watersheds in British Colombia, Canada. Similarly, Cooley et al (Cooley et al, 2014) found that the likelihood of isolating L. monocytogenes from California surface water samples was significantly higher in winter and spring compared to summer and fall.…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, Cooley et al (Cooley et al, 2014) found that the likelihood of isolating L. monocytogenes from California surface water samples was significantly higher in winter and spring compared to summer and fall. Falardeau et al (Falardeau et al, 2017) and Cooley et al (Cooley et al, 2014) attributed these seasonal trends in L. monocytogenes isolation to increased rainfall and lower temperatures in winter and spring compared to summer and fall. In our study, the likelihood of isolating L. monocytogenes in NY (i) was also associated with temperature, and (ii) decreased as air temperature increased from May to June and increased as air temperature decreased from July to September.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations